Dissolution of diopside and basaltic glass: The effect of carbonate coating - Stockmann, G.; Wolff-Boenisch, Domenik; Gíslason, S.; Oelkers, E. (2008)
Far-from-equilibrium dissolution experiments with diopside and basaltic glass in mixed-flow reactors at 70°C and pH 8.2 show that solute concentrations do not reach steady state over the experimental duration of 45-60 days. Chemical modelling indicates that during the dissolution experiments, solutions have become supersaturated with respect to carbonates in the case of diopside, and carbonates, clay minerals and zeolites in the case of the basaltic glass. Decreasing dissolution is therefore interpreted as a result of secondary surface precipitates blocking the reactive surface area. Calcite formation was supported in both experiments by a significant increase in Ca (and Sr) concentrations as pH was abruptly lowered from 8.2 to 7 because this change increased carbonate solubility and caused all potential carbonate precipitates to re-dissolve. The reduction in pH also led to an increase in Si concentration for diopside and a decrease in Si concentration for basaltic glass. This observation is in accordance with previous experiments on the pH-dependent dissolution rates of pyroxenes and basaltic glass. © 2008 The Mineralogical Society.